New promotion criteria for academics: a case of University Teknologi Mara / Fauziah Noordin … [et al.] - Noordin, Fauziah; Ariffin, Junaidah; Ahmad, Jasmine; Daud, Normala; Ibrahim, Saadah; Wan Ismahanini Ismail, Hanim Azura Mahyudin (Research Management Institute (RMI), 2012)
A university is said to be defined by its system of promotion. Designing a promotion system and participating in its decisions are two of the most important ways in which each academic shapes the university. The promotion system reflects two overlapping but distinct sets of values, namely, those of the various disciplines and those of the institution. In June 2010, the Deputy Vice Chancellor of Academic and International appointed a university task force on new promotion criteria to revise and develop promotion criteria with the purpose of maintaining high academic standard that are consistent to current changes and needs of UiTM…